E-Learning Using the Flipped Classroom Model-Based Teachmint Application and its Impact on Student Science Learning Outcomes - Kurniawan, Romi; Fitria, Yanti (International Journal of Elementary Education, 2023)
The lack of teachers' ability to create science learning media that is integrated with technology and information for grade V elementary schools prompted this research. The purpose of this research is to create a valid, practical and effective e-Learning product for the fifth grade science class in elementary schools. The research method used is Research and Development and refers to the ADDIE development model. Data collection techniques are divided into 2, specifically Qualitative and Quantitative data. Qualitative data had been received from suggestions and comments by means of validators and practitioners. The media became validated by 2 material professional lecturers, 2 media professional lecturers, and 1 language professional lecturer, and tested by 2 instructors and 10 students for practicality, and 31 college students for effectiveness. Quantitative information was acquired from the results of validator and practitioner questionnaire exams. Data analysis techniques uses a Likert scale and a paired sample t-test. The results of the validation and testing of science lessons show that the Media Media e-Learning based on the Flipped Classroom Model using the Teachmint application on Ecosystem Theme 5 is said to be very valid with a score of 91, very practical with a value of 92.5 and very effective 92.1. Based on the results of the data acquisition, it shows that e-Learning using the Teachmint application for science learning outcomes is considered very valid, very practical, and very effective in learning science in elementary schools.